FACTORS THAT INFLUENCE STUDENT SATISFACTION IN USINGE-LEARNING MEDIA DURING THE CORONA PANDEMICPERIOD - Mohammad Rizal Gaffar; Chandra Budhi Septyandi (Politeknik Negeri Media Kreatif, 2020)
The Corona pandemic has spread almost everywhere in the world. Indonesia became one of the affected countries. The education sector became one of the affected sectors and changed the learning process, which was initially dominated by conventional learning into E-Learning based learning. This sudden change makes all components of learning, especially teachers and instructors, have to adapt to use the facilities available. However, this sudden change inevitably creates obstacles to the achievement of learning objectives. Therefore, it is considered important to evaluate the learning process through this e-learning facility so that teaching participants can feel satisfied and the learning objectives are achieved. The research method used is a mixed method method by conducting a qualitative method first to design a model of insight obtained from interviews with respondents then using quantitative methods to obtain statistical values to strengthen the proposed model.A total of 153 respondents' data were processed using Partial Least Square software. The results of data processing prove model is valid and reliable. The model has strong predictive power. From four proposed variables, Perception Ease of Use, Perception Usefulness, and Facilitating Condition have a significant positive effect on User Satisfaction (students). And student satisfaction has a significant positive effect on the future use of e-learning media behavior.